Surface quality produced in EDM with tungsten carbide and copper compacted electrodes - Khan, Ahsan Ali; Mohammed, Baba Ndaliman; Mohamad, Ummu Atiqah Khairiyah; Sulong, Nurul Farhana; Mohd Zain, Zakaria (Trans Tech publication, 2015)
Electrical discharge machining (EDM) is one of the most commonly used technique to machine very hard materials. Materials like hardened tool steels, titanium and its alloys and difficult-to-machine materials can be easily processed with EDM. The machining performance to a great extent depends on the composition of the electrode. This paper presents the machining performance of powder metallurgy (PM) compacted electrodes made from titanium carbide (TiC) and copper (Cu) powders. The Cu-TiC electrodes made up of 70% of TiC and 30% of Cu powders. They were compacted at a pressure of 6,000 psi (41.34 MPa). Mild steel was used as the workpiece material. Machining was conducted with the peak current, pulse-on time and pulse-off time as the electrical input variables. The output variables of the investigation were work surface roughness and its hardness. It was found that work surface roughness increases with increase in current and pulse-on-time. However, it decreases with increase in pulse-off time. It was found that the highest value of surface roughness (14.782 μm) was found at highest peak current (6.5 A), highest pulse on-time (7.5 μs) and lowest pulse-off time (6.5 μs). The highest value of surface hardness (57.3 BHB) was found at the same machining conditions. The smoothest surface (14.782 μm) was found at the lowest peak current (3.5 A), lowest pulse on-time (6.0 μs) and highest pulse-off time (8.5 μs). The lowest value of surface hardness (42.9 BHB) was found at the same machining conditions.